Simulation of spatially varying seafloor motions using onshore earthquake recordings - Li, C.; Li, H.; Hao, Hong; Bi, Kaiming (2018)
Compared to the seismic motions recorded on the onshore sites, the quantity of offshore earthquake recordings is very limited. This paper presents a novel method to simulate spatially varying ground motions at multiple seafloor sites by using the more abundant onshore earthquake records. A pair of onshore and offshore seismic motions recorded in the same earthquake event is selected, and the onshore recording is employed as the predefined motion to simulate offshore seismic motions. The detailed information of the onshore and offshore sites beneath respective stations is collected, and the ground motion transfer functions are computed by including the effects of seawater and soil saturation on the seismic P wave propagation. Using the power spectral density (PSD) functions of the onshore recording and the onshore and offshore site transfer functions, the ground motion PSD functions on the offshore site are estimated, and the threecomponent seafloor seismic motions are synthesized. The basic characteristics of the synthesized seafloor motions are compared with the seafloor recording, and the feasibility of the proposed method is validated. Finally, the approach is further extended to the simulation of spatially varying seafloor motions by considering the spatial variation between the seafloor motions at various offshore sites. The effect of local offshore site on the lagged coherency of spatial seafloor motions is also investigated.